Review: Speciation in the myrtle family (Myrtaceae): rapid and slow models - PUDJI WIDODO (Society for Indonesian Biodiversity, 2007)
Speciation or formation of new species is a process which may take very long time. When a new species is really formed from a previous species is still unknown exactly. However, sometimes when populations no longer interbreed, they are thought to be separate species. As natural selection, if populations adapt the occupying different environments, they will diverge into races, subspecies, and finally separate species. There are some models of speciation such as geographical, polyploidy, chromosomal, and ecological speciation. However, in the myrtle family (Myrtaceae) they can be grouped into two big models of speciation namely the rapid and slow speciation. This review points out that hybridization is a major factor affecting Myrtaceae, although evolution activities were also approved by the fact that some fossil pollens have been found in AntarticaÂ© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words:.speciation models, mutation, evolution, Myrtaceae